Portable and sensitive approach for hydrazine detection via silver nanoparticles formation: A novel approach for chemical sensing - Sarzamin Khan; Zaibi Zaibi; Muhammad Nasimullah Qureshi; Carlos A.T. Toloza; Eman Alzahrani; Syed Sheraz Ahmad; Leonardo S.G. Teixeira (MethodsX)
A novel silver nanoparticle (AgNPs) based sensor for hydrazine detection is introduced, offering enhanced sensitivity, selectivity and a swift response time. The sensing mechanism relies on the reduction of silver ions in the presence of analyte (hydrazine), leading to the formation of silver nanoparticles under optimized conditions, producing a distinct and intense surface plasmon resonance signal. Moreover, the distinct color variations have been quantitatively assessed through RGB (red, green, and blue, primary component of light) values by smartphone, allowing its functionality as a portable hydrazine sensor. The proposed sensing strategy is highly sensitive, does not rely on complex equipment, and is applicable for field based hydrazine analysis in industrial and natural water systems. • Indirect colorimetric detection of hydrazine using in situ synthesize silver nanoparticles • Integration with smartphone enables portable, on-site detection of hydrazine • Enhanced selectivity and sensitivity, make the sensor ideal for hydrazine monitoring in environmental samples